Perancangan Sistem Informasi Penilaian Kinerja Karyawan Berbasis Web Menggunakan Metode RUP pada PT. Cinta Food - Muhammad Masngudi; Halimah, Halimah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the implementation of a web-based employee performance appraisal system at PT. Cinta Food, focusing on effectiveness, consistency, and administrative efficiency. The research employed a case study design with a descriptive quantitative approach, supported by system testing using the blackbox method. Findings reveal that the implementation of the web-based system reduced the performance appraisal process from 14 days to 4 days, achieving a 71.43% efficiency gain. The consistency rate between appraisers increased from 78% to 95%, indicating a significant reduction in subjective bias. Additionally, the administrative workload in the HRD division decreased by up to 60% due to automated archiving and integration of attendance data with performance targets. The system’s audit trail feature enhanced transparency and simplified dispute resolution. These results align with previous studies highlighting the benefits of digitizing performance appraisals to improve accuracy and speed. The findings are expected to serve as a reference for other organizations aiming to optimize performance evaluation systems through information technology.